(untitled) (European Journal of Formal Sciences and Engineering, 2019)
Hashgraph is data structure and consensus algorithm that is fast, with a very high throughput and low consensus latency, secure because of the asynchronous byzantine fault tolerant and fair due to the fairness of access, ordering, and timestamps. These properties enable new decentralized applications such as a stock market, improved collaborative applications, games, and auctions. Hashgraph is a new consensus protocol that has garnered attention lately by being projected as a technology that will make blockchains obsolete. Hashgraph currently scales only in the number of transactions processed but does not scale with the number of nodes in the network. Hashgraph will face the same issues that other public blockchains are facing today and may not be able to maintain its security and performance. In fact, scalability is still an open problem for public blockchains.